ANALISIS PEMASARAN KARET SISTEM LELANG DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Al Fatah, Aung Ezra; Rosnita, Rosnita; Sayamar, Eri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The goal of this research is learning about : 1) identify rubber farmers’ profile in Kecamatan Gunung Toar, 2) study about auction system of rubber marketing in Kecamatan Gunung Toar, 3) analyze cost, marketing margin and profif jn auction system of marketing in Kecamatan Gunung Toar. This research in Kecamatan Gunung Toar with 39 rubber farmers is using survey method. This analysis is using descriptive analysis. The result of this research shows that rubber farmers’ profile who use auction system of marketing are 79.90 % of men with productive age number that is 71.70%, average education of farmers is high school with 51.20%, number of family dependents are within 0 to 3 with 89.70%, the extensive land holdings of farmers is dominant in higher than 2 hectares with 56.40% and the status of own land is 100% and also experience period of  farmers’ farming is 16 to 20 years with 53.80%. The result in auction system of rubber is market that held in every Monday 10:00 to 20:00 o’clock, start with latex collecting until giving money to farmers. The result in cost, margin, and the profit in auction system of rubber marketing to farmers’ margin is 1.200 in average, farmers’ cost is 759,35 in average and wholesalersprofit is 400,00 in average, they are all in kilogram and month calculation.Keyword : auction marketing, rubber, farmer